Approaches to Reduce or Eliminate the Risks of Sight Tests in Alberta: A Jurisdictional Review - Anderson, Alyssa Erin; Hensel, Gordon (Canadian Journal of Optometry, 2021)
This research report is motivated by two independent case reports featuring individuals living in Alberta, Canada who experienced permanent vision loss as a result of inadequate standards of practice surrounding sight tests. Sight tests are usually performed by opticians and are conducted independently of a comprehensive eye exam. A description of the two case reports in addition to a discussion of the potential dangers of sight tests provide evidence of the public health risks associated with sight tests. To investigate potential approaches to reduce or eliminate the risks of sight tests in Alberta, we conducted a jurisdictional review examining the laws and standards of practice governing sight tests in Canada, the United States, New Zealand, and the United Kingdom. Based on the jurisdictional review, the outright prohibition of sight tests in Alberta may be the best approach to protect the public interest and reduce cases of avoidable vision loss. As seen in other Canadian provinces, alternative approaches to reduce the risk of sight tests may involve 1) developing and enforcing restrictions around the performance of sight tests or 2) developing clearly defined scenarios in which opticians can collaborate with authorized prescribers to deliver safe sight tests.